Business English Writing (BEW) Training for Students of SMK PGRI Sukoharjo Majoring in OTKP (Automation and Office Governance) - Sihindun Arumi; Giyatmi (PT FORMOSA CENDEKIA GLOBAL, 2023)
This training aims to equip class X students majoring in OTKP at SMK PGRI Sukoharjo with the ability to write business letters in English. The training participants were class X OTKP students at SMK PGRI Sukoharjo. Training was carried out using three meetings. Training is carried out online using Google Meet (first meeting) and face to face in class (second and third meetings). The first meeting includes a pre-test and material related to Parts of Business Letters in English. The second meeting is the Sales Letter. The third meeting was Order Letter and post-test material. The average of the pre-test is 20 while the average of the post-test is 85. Based on the pre and post test scores, there is a significant increase in the average score. This shows that this training can improve students' abilities in writing business letters.